How do nurses facilitate shared decision making in HIV care?: an exploratory study of UK nurses knowledge, perspective and experience of facilitating shared decision making in clinical practice - Croston, Michelle; McLuskey, John; Evans, Catrin (European Society for Person Centered Healthcare, 2016)
Shared Decision Making (SDM) enables clinicians to promote self-management and to empower patients with long-term health conditions. Whilst it has been reported in other health conditions, there is little empirical research on the nature and practice of SDM in HIV care. This project aimed to explore current views and practices amongst UK HIV Nurses regarding SDM. A mixed methods study utilised focus groups and an online survey to identify opportunities, challenges and training needs. Nurses are supportive of SDM but face patient related, organisation and health system challenges to implement it, especially in supporting complex patients. SDM is an important aspect of nursing care for people living with HIV. Nurses need more training and resources to implement SDM effectively. In order to develop such training and resources to better understand SDM in relation to HIV care, there is a need for research on patient perspectives and experiences in this area.